T-BEST APPROXIMATION IN FUZZY AND INTUITIONISTIC FUZZY METRIC SPACES - Golshan, H. M.; Naraghi, H.; Kazemi, M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we introduce and extend some notions in [18] and introduce a notion of t-best approximatively compact sets, t-best approximation points, t-proximinal sets and boundedly compact sets in both fuzzy and intuitionistic fuzzy metric spaces. The results obtained in this paper are related to the corresponding results in metric spaces and fuzzy metric spaces and fuzzy normed space. Many examples are also given.